Aripiprazole-induced transient myopia - Cumurcu, Tongabay (North Clin Istanb, 2019)
This study aims to present a case of transient myopia due to aripiprazole used in the treatment of depression. A 21-year-old female who was being treated for depression with 15 mg/day Aripiprazole during two months. She normally used -3.75 D glasses. She was admitted to our outpatient clinic with sudden onset blurring of vision in both eyes despite using glasses for about three days. Using of aripiprazole was observed in the patient’s history. She was found to have myopia of -6.0 diopters in both eyes with measurement of otorefractometer; her visual acuity was 6/10 in both eyes with her glasses. The other eye examination findings of the patient were normal. The drug was discontinued, and the patient was followed. One mount later on examination, the patient’s visual acuity increased to 10/10 in both eyes. Following the first day of the Alx values measured were 0.3 mm longer than one month after the measurement; the minimal difference between the other anterior segment findings were recorded. Although the specific mechanisms that cause acute myopia has not been fully revealed, it can be ciliary spasm, ciliary bodies effusion, peripheral uveal effusion and effects of ocular serotonergic intraneural fibers. We believe that it would be important for clinicians. They should keep in mind these conditions when prescribing aripiprazole and need to inform patients about the side effects related to the eye.